Misdiagnosis of Acute Myocardial Infarction: A Systematic Review of the Literature. Issue 3 (17th February 2021) - Kwok, Chun Shing; Bennett, Sadie; Azam, Ziyad; Welsh, Victoria; Potluri, Rahul; Loke, Yoon K.; Mallen, Christian D.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Despite the availability of tests to diagnose acute myocardial infarction (AMI), cases are still missed. Methods: We systematically reviewed the literature to determine how missed AMI has been defined, the reported rates of misdiagnosed AMI, the outcomes patients with misdiagnosed AMI have, what diagnosis was initially suspected in missed AMI cases, and what factors are associated with misdiagnosed AMI. We searched MEDLINE and EMBASE in September 2020 for studies that evaluated missed AMI. Data were extracted from studies that met the inclusion criteria and the results were narratively synthesized. Results: A total of 15 studies were included in this review. The number of patients with missed AMI in individual studies ranged from 64 to 4707. There was no consistently used definition for misdiagnosed AMI, but most studies reported rates of approximately 1%–2%. Compared with AMI that was recognized, 1 study found no difference in mortality for misdiagnosed AMI at 30 days and 1 year. The common initial misdiagnoses that subsequently had AMI were ischemic heart disease, nonspecific chest pain, gastrointestinal disease, musculoskeletal pain, and arrhythmias. Reasons for missed AMI include incorrect electrocardiogram interpretation and failure to order appropriate diagnostic tests. Hospitals in rural areas and those with a low proportion of classical chest pain patients that turned out to have AMI were at greater risk of missed AMI. Conclusions: Misdiagnosed AMI is an unfortunate part of everyday clinical practice and better training in electrocardiogram interpretation, and education about atypical presentations of AMI may reduce the number of misdiagnosed AMIs.